Layered metal-organic chalcogenide thin films for flexible and large-area X-ray direct detection - Fratelli, Ilaria; Maserati, Lorenzo; Basiricò, Laura; Galeazzi, Alessandro; Passarella, Bianca; Ciavatti, Andrea; Caironi, Mario; Fraboni, Beatrice (Frontiers in Physics, 2023)
X-ray detection for personal dosimetry requires sensitive, stable and non-toxic materials. At the same time, scalability onto large-area and flexible substrates is emerging as a desirable property. To satisfy these requirements, novel materials to be employed as the active layer of direct X-ray detectors are needed. In this search for easy-processability, large area, efficient and non-toxic materials for direct X-ray detection, we assess the performance of a layered metal-organic chalcogenide [AgSePh]∞, recently proposed as representative of a novel excitonic semiconductors platform. Here we demonstrate that [AgSePh]∞ can be successfully applied as direct ionizing radiation detecting layer, reaching sensitivities up to (180 ± 10) µC Gy -1 cm -2 and competitive limit of detection down to (100 ± 30) nGy s -1 . Moreover, it offers good stability and reproducibility of detection after 100 Gy of irradiation and upon bending to a curvature radius of 5 mm.Layered metal-organic chalcogenide thin films for flexible and large-area X-ray direct detection